Answer:
2.
A. (P+h)(x)
2x/x+4 (x-1) + x/x-1 (x+4)
2x^2-1/x^2-4
+
X^2+4/x^2-4
= 3x^2+3/x^2-4
B. (F-g)(x)
X^2-7x+6-x - 6
= x^2 -8x
C. (Fg)(x)
(X^2-7x+6)(x-6)
= x^3-13x^2+48x-36
D. (H/p)(x)
X/x-1 / 2x/x+4
X/x-1 / x+4/2x
= X^2+4x/2x^2-2x
3.
A. (F+g)(3)
X^2+1 + x-4
3^2+1 + 3-4
10 -1
= 9
B. (f-g)(0)
X^2+1 - x-4
0+1 -0-4
1-4
= -3
C. (Fg)(-k)
(X^2+1) (x-4)
(-k^2+1) (-k-4)
K^3+4k^2-k-4
D. (F/g)(k-2)
X^2+1 /x-4
K-2^2+1 / k-2 -2
= K^2-4k+5 / k-4
Step-by-step explanation:
Here is your answer.........
Answer:
<em>( About ) 1.77 seconds; Option B</em>
Step-by-step explanation:
We are given the equation h ( t ) = - 16t^2 + 50, so in order to determine the time let us determine the x - intercept for y ⇒ 0;
- 16t^2 + 50 = 0,
- 16t^2 = - 50,
t^2 = 25 / 8,
Thus t ⇒ √ ( 25 / 8 ), and t ⇒ - √ ( 25 / 8 ),
t ⇒ ( 5√2 )/ 4, and - ( 5√2 )/ 4,
But time is represented only by a positive value, thus
t ⇒ ( 5√2 )/ 4 = 1.767766953......., ( About ) 1.77 seconds
<em>Answer; ( About ) 1.77 seconds; Option B</em>
Law of cosine:
c² = a² +b² -2ab*cosC.
Because the triangle is equilateral a=b=c=x,
and we can write,
x²=x² +x² -2xx*cosC
x² =2x² -2x²* cos C
-x² = -2x²*cos C
cos C= 1/2,
so m∠C=60⁰.
Because all sides are equal, and across of the equal sides should be equal angles, all angles will be also equal and = 60⁰.
Answer:
A
Step-by-step explanation:
based on exonent rule (#^x)^y=#^xy